Which equation is equivalent to the equation below, when solved for y?

2(x + y) - z = 2x + z

A.) y = 1

B.) y = z

C.) y = 1 + 4x

D.) y = z + 4x

2(x + y) - z = 2x + z

A.) y = 1

B.) y = z

C.) y = 1 + 4x

D.) y = z + 4x

2(x + y) - z = 2x + z

2x + 2y - z = 2x + z {used distributive property}

2y = 2z {subtracted 2x and added z to each side}

y = z {divided each side by 2}

2x + 2y - z = 2x + z {used distributive property}

2y = 2z {subtracted 2x and added z to each side}

y = z {divided each side by 2}

**B.) y = z****Ask Algebra House**